2021
DOI: 10.1371/journal.pone.0255242
|View full text |Cite
|
Sign up to set email alerts
|

A 50 Hz magnetic field affects hemodynamics, ECG and vascular endothelial function in healthy adults: A pilot randomized controlled trial

Abstract: Application of exposure to 50/60 Hz magnetic fields (MFs) has been conducted in the treatment of muscle pain and fatigue mainly in Japan. However, whether MFs could increase blood flow leading to muscle fatigue recovery has not been sufficiently tested. We investigated the acute effects of a 50 Hz sinusoidal MF at Bmax 180 mT on hemodynamics, electrocardiogram, and vascular endothelial function in healthy young men. Three types of regional exposures to a 50 Hz MF, i.e., forearm, upper arm, or neck exposure to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…(a) Relationship between magnetic flux density and distance from the center of a magnetic field (MF) coil. The MF strength decays with distance from the coil (Okano et al, 2021). (b) Examination of optimal conditions for health promotion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(a) Relationship between magnetic flux density and distance from the center of a magnetic field (MF) coil. The MF strength decays with distance from the coil (Okano et al, 2021). (b) Examination of optimal conditions for health promotion.…”
Section: Resultsmentioning
confidence: 99%
“…(a) Relationship between magnetic flux density and distance from the center of a magnetic field (MF) coil. The MF strength decays with distance from the coil (Okano et al, 2021) do this, we estimated magnet field decay with distance from the AC magnetic field generator (Figure 1a). In this way, AC magnetic field intensity is gradually attenuated with distance from the field generator.…”
Section: Determination Of the Optimal Magnetic Field Strengthmentioning
confidence: 99%
“…In recent years, EMF therapy has gained significant interest due to its potential protective impact on cardiovascular functions, and various in vivo experiments on humans have been conducted. For instance, a pilot randomized controlled trial on healthy adults showed that a magnetic field of 50 Hz had therapeutic effects to stimulate parasympathetic activity, resulting in enhanced vasodilation and blood flow through a nitric oxide-dependent mechanism (Okano et al, 2021 ). A double-blind, repeated study explored the effect of ELF-EMFs on heart rate (HR) and HR variability and found a reduction in HR caused by the possible enhancement of parasympathetic predominance by short-term EMF (Binboga et al, 2021 ).…”
Section: Effects Of Elf-emfs On Biological Activities On the System L...mentioning
confidence: 99%
“…Recently, a prospective, randomized, sham‐controlled study (UMIN Clinical Trial Registry [CTR] UMIN000038834) involving healthy young men examined the acute effects of a 50 Hz EMF on hemodynamic responses. In addition to significant increases in ulnar artery blood flow due to regional exposure to EMF, the results of the flow‐mediated dilation (FMD) test demonstrated an increase in NO production and NO‐mediated vasodilation under exposure to EMF exposure 27 . Shear stress can induce the expression of COX‐2/PGI 2 in endothelial cells, which plays a crucial role in maintaining thromboembolic equilibrium 28 .…”
Section: Therapeutic Value Of Emf‐based Modalitiesmentioning
confidence: 99%
“…In addition to significant increases in ulnar artery blood flow due to regional exposure to EMF, the results of the flow-mediated dilation (FMD) test demonstrated an increase in NO production and NOmediated vasodilation under exposure to EMF exposure. 27 Shear stress can induce the expression of COX-2/PGI 2 in endothelial cells, which plays a crucial role in maintaining thromboembolic equilibrium. 28 In a FeCl 3 -induced thrombosis, which is related to platelet activation and coagulation system activation, various intensities of exposure to SMF were tested (200, 400, and 600 mT), the results showed that SMF with an intensity of 600 mT significantly increased PAI (plasminogen activator inhibitor) and tPA (tissue-type plasminogen activator) activity and decreased the content of thrombus protein content.…”
Section: Altering Hemodynamic Factorsmentioning
confidence: 99%